Experimental testing for metrological traceability and accuracy of liquid microflows and microfluidics. (March 2020) - Batista, Elsa; Sousa, João A.; Cardoso, Susana; Silvério, Vânia
Abstract: Micro-flows are growing more important and useful for a wide variety of scientific and engineering fields such as bioanalysis, drug development and administration, Organ-on-a-Chip, etc, but accurate and reliable measurements traceable to the International System of Units can be challenging in micro-to-femto flow operating ranges. In this paper a gravimetric method has been used to quantify the measurement error of the volumetric flow rate of water from 1000 μL/h to 1 μL/h delivered by a syringe pump in different experimental conditions that replicate the current microfluidics setups. Several sources of error have been determined such as the mass measurement, the fluid evaporation dependent on the gravimetric methodology implemented and the repeatability, believed to be closely related to the operating mode of the stepper motor and drive screw pitch of the syringe pump. The elastic deformability of the medical grade 1 mL polypropylene syringes commonly used in micro-flows has greatly affected the volumetric flow rate, unlike the glass syringes tested. Finally, testing the gravimetric method while adding PDMS microfluidic channels to the flow circuit served to demonstrate that material, dimensions and shape of the microchannels did not show significant influence on the volumetric flow rate error for the flow rates imposed, important to establish well defined methodologies for microfluidics. Highlights: Micro-flows are growing more important and useful for a wide variety of scientific and engineering fields and especially microfluidic applications. In this work results show that the error obtained using Polypropylene syringes to infuse liquid in microfluidic channels is considerably higher than that obtained with glass syringes, due to the compliance effect. This work indicates that PP syringes should not be used in micro-flow calibration or in flow generators without previous calibration of the whole setup because the programmed flow will differ in a great extent from the real flow.